Au(III) complexes with tetradentate-cyclam-based ligands - Reiersølmoen, Ann Christin; Solvi, Thomas N.; Fiksdahl, Anne (Beilstein Journal of Organic Chemistry, 2021)
Chiral cyclam (1,4,8,11-tetraazacyclotetradecane) derivatives were synthesized stepwise from chiral mono-Boc-1,2-diamines and (dialkyl)malonyl dichloride via open diamide-bis(N-Boc-amino) intermediates (65–91%). Deprotection and ring closure with a second malonyl unit afforded the cyclam tetraamide precursors (80–95%). The new protocol allowed the preparation of the target cyclam derivatives (53–59%) by a final optimized hydride reduction. Both the open tetraamine intermediates and the cyclam derivatives successfully coordinated with AuCl3 to give moderate to excellent yields (50–96%) of the corresponding novel tetra-coordinated N,N,N,N-Au(III) complexes with alternating five- and six-membered chelate rings. The testing of the catalytic ability of the cyclam-based N,N,N,N-Au(III) complexes demonstrated high catalytic activity of some complexes in selected test reactions (full conversion in 1–24 h, 62–97% product yields).
Keywords: Au(III); carboalkoxylation; coordination studies; cyclam derivatives; cyclopropanation

(untitled) - Corma, A.; Leyva-Pérez, A.; Sabater, M. J. (Chem. Rev., 2011)

(untitled) - Hashmi, A. S. K.; Buehrle, M. (Aldrichimica Acta, 2010)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Commun., 2007)

(untitled) - Li, Z.; Brouwer, C.; He, C. (Chem. Rev., 2008)

(untitled) - Nevado, C. (Chimia, 2010)

(untitled) - Sengupta, S.; Shi, X. (ChemCatChem, 2010)

(untitled) - Gorin, D. J.; Sherry, B. D.; Toste, F. D. (Chem. Rev., 2008)

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Mascareñas, J. L.; Varela, I.; López, F. (Acc. Chem. Res., 2019)

(untitled) - Mato, M.; García‐Morales, C.; Echavarren, A. M. (ChemCatChem, 2019)

(untitled) - García-Morales, C.; Echavarren, A. M. (Synlett, 2018)

(untitled) - Wang, Y.-M.; Lackner, A. D.; Toste, F. D. (Acc. Chem. Res., 2014)

(untitled) - Obradors, C.; Echavarren, A. M. (Chem. Commun., 2014)

(untitled) - Dorel, R.; Echavarren, A. M. (Chem. Rev., 2015)

(untitled) - Zi, W.; Dean Toste, F. (Chem. Soc. Rev., 2016)

(untitled) - Kimura, E.; Kurogi, Y.; Takahashi, T. (Inorg. Chem., 1991)

(untitled) - Kavaklı, C.; Özvatan, N.; Tuncel, S. A.; Salih, B. (Anal. Chim. Acta, 2002)

(untitled) - Yau, J.; Mingos, D. M. P.; Powell, H. R. (Polyhedron, 1996)

(untitled) - Kimura, E.; Kurogi, Y.; Koike, T.; Shionoya, M.; Iitaka, Y. (J. Coord. Chem., 1993)

(untitled) - Nardin, G.; Randaccio, L.; Annibale, G.; Natile, G.; Pitteri, B. (J. Chem. Soc., Dalton Trans., 1980)

(untitled) - Cinellu, M. A.; Minghetti, G.; Pinna, M. V.; Stoccoro, S.; Zucca, A.; Manassero, M. (J. Chem. Soc., Dalton Trans., 2000)

(untitled) - Carotti, S.; Guerri, A.; Mazzei, T.; Messori, L.; Mini, E.; Orioli, P. (Inorg. Chim. Acta, 1998)

(untitled) - Navarro, M. (Coord. Chem. Rev., 2009)

(untitled) - Gabbiani, C.; Casini, A.; Messori, L. (Gold Bull., 2007)

(untitled) - Messori, L.; Orioli, P.; Tempi, C.; Marcon, G. (Biochem. Biophys. Res. Commun., 2001)

(untitled) - Casini, A.; Hartinger, C.; Gabbiani, C.; Mini, E.; Dyson, P. J.; Keppler, B. K.; Messori, L. (J. Inorg. Biochem., 2008)

(untitled) - Marcon, G.; Messori, L.; Orioli, P.; Cinellu, M. A.; Minghetti, G. (Eur. J. Biochem., 2003)

(untitled) - Sun, R. W.-Y.; Che, C.-M. (Coord. Chem. Rev., 2009)

(untitled) - Messori, L.; Abbate, F.; Marcon, G.; Orioli, P.; Fontani, M.; Mini, E.; Mazzei, T.; Carotti, S.; O'Connell, T.; Zanello, P. (J. Med. Chem., 2000)

(untitled) - Schneider, C. R.; Lewis, L. C.; Shafaat, H. S. (Dalton Trans., 2019)

(untitled) - Mash, B. L.; Raghavan, A.; Ren, T. (Eur. J. Inorg. Chem., 2019)

(untitled) - Nichols, E. M.; Chang, C. J. (Organometallics, 2019)

(untitled) - Burrows, C. J.; Muller, J. G.; Poulter, G. T.; Rokita, S. E. (Acta Chem. Scand., 1996)

(untitled) - Boiocchi, M.; Ciarrocchi, C.; Fabbrizzi, L.; Licchelli, M.; Mangano, C.; Poggi, A.; Vázquez López, M. (Inorg. Chem., 2015)

(untitled) - Shircliff, A. D.; Wilson, K. R.; Cannon-Smith, D. J.; Jones, D. G.; Zhang, Z.; Chen, Z.; Yin, G.; Prior, T. J.; Hubin, T. J. (Inorg. Chem. Commun., 2015)

(untitled) - De, C. K.; Paul, A.; Emge, T. J.; Seidel, D. (Supramol. Chem., 2016)

(untitled) - Dogan, A.; Schwederski, B.; Schleid, T.; Lissner, F.; Fiedler, J.; Kaim, W. (Inorg. Chem. Commun., 2004)

(untitled) - Yang, T.; Tu, C.; Zhang, J.; Lin, L.; Zhang, X.; Liu, Q.; Ding, J.; Xu, Q.; Guo, Z. (Dalton Trans., 2003)

(untitled) - Fan, D.; Yang, C.-T.; Ranford, J. D.; Vittal, J. J. (Dalton Trans., 2003)

(untitled) - Kilpin, K. J.; Henderson, W.; Nicholson, B. K. (Dalton Trans., 2008)

(untitled) - Hill, D. T.; Burns, K.; Titus, D. D.; Girard, G. R.; Reiff, W. M.; Mascavage, L. M. (Inorg. Chim. Acta, 2003)

(untitled) - Cheung, T.-C.; Lai, T.-F.; Che, C.-M. (Polyhedron, 1994)

(untitled) - Reiersølmoen, A. C.; Csókás, D.; Pápai, I.; Fiksdahl, A.; Erdélyi, M. (J. Am. Chem. Soc., 2019)

(untitled) - Johnson, M. W.; DiPasquale, A. G.; Bergman, R. G.; Toste, F. D. (Organometallics, 2014)

(untitled) - Reiersølmoen, A. C.; Csókás, D.; Øien-Ødegaard, S.; Vanderkooy, A.; Gupta, A. K.; Carlsson, A.-C. C.; Orthaber, A.; Fiksdahl, A.; Pápai, I.; Erdélyi, M. (J. Am. Chem. Soc., 2020)

(untitled) - Reiersølmoen, A. C.; Fiksdahl, A. (Eur. J. Org. Chem., 2020)

(untitled) - Dubé, P.; Toste, F. D. (J. Am. Chem. Soc., 2006)

(untitled) - Zi, W.; Toste, F. D. (J. Am. Chem. Soc., 2013)

(untitled) - Sperger, C. A.; Tungen, J. E.; Fiksdahl, A. (Eur. J. Org. Chem., 2011)

(untitled) - Iqbal, N.; Sperger, C. A.; Fiksdahl, A. (Eur. J. Org. Chem., 2013)

(untitled) - Reiersølmoen, A. C.; Østrem, E.; Fiksdahl, A. (Eur. J. Org. Chem., 2018)

(untitled) - Johansson, M. J.; Gorin, D. J.; Staben, S. T.; Toste, F. D. (J. Am. Chem. Soc., 2005)